2007
DOI: 10.1021/jo070739s
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Binding in HDAC Inhibitors:  A DFT Study

Abstract: Histone deacetylases (HDACs) are attractive targets for the treatment of cancers and a variety of other diseases. Most currently studied HDAC inhibitors contain hydroxamic acids, which are potentially problematic in the development of practical drugs. DFT calculations of the binding modes and free energies of binding for a variety of other functionalities in a model active site of HDAC are described. The protonation state of hydroxamic acids in the active site and the origin of the high affinity are discussed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
97
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(104 citation statements)
references
References 17 publications
6
97
1
Order By: Relevance
“…In addition, in some of these studies, the role played by the basic neighboring residues was not considered. 36 An exhaustive survey of the PDB led us to collect 121 structures of metalloenzymes bound to various ligands and with most having a resolution lower than 2.5 Å. The ligands cover a number of zinc binding groups (e.g., oamidoaniline, terminal sulfonamides, hydroxamic acids, thiols), and even include ligands bearing two potential zinc binding groups such as captopril cocrystallized with the angiotensin converting enzyme (pdb code: 2x8z, Figure 5) or a sulfanyl butanoic acid derivative (3i1u).…”
Section: Journal Of Chemical Information and Modelingmentioning
confidence: 99%
“…In addition, in some of these studies, the role played by the basic neighboring residues was not considered. 36 An exhaustive survey of the PDB led us to collect 121 structures of metalloenzymes bound to various ligands and with most having a resolution lower than 2.5 Å. The ligands cover a number of zinc binding groups (e.g., oamidoaniline, terminal sulfonamides, hydroxamic acids, thiols), and even include ligands bearing two potential zinc binding groups such as captopril cocrystallized with the angiotensin converting enzyme (pdb code: 2x8z, Figure 5) or a sulfanyl butanoic acid derivative (3i1u).…”
Section: Journal Of Chemical Information and Modelingmentioning
confidence: 99%
“…Such a pK a would guarantee that the hydroxamate is neutral in solution at physiological pH, facilitating cell membrane permeation. However, upon coordination of the zinc ion, the pK a of hydroxamic acids would be reduced by approximately three units, the acidic proton being transferred to the adjacent conserved histidine (H669 in HDAC7) [80]. Interestingly, computational studies [41,66,[81][82][83] indicate that the anionic hydroxamate chelates the zinc ion in a bidentate fashion with geometries close to the experimental ones.…”
Section: Structural Features Important For Binding and Selectivity Ofmentioning
confidence: 74%
“…As for the zinc-binding ability of thiol, the results of density functional theory calculations suggested that the zinc-binding affinity of thiol is lower than that of hydroxamic acid. 84,85) On the hypothesis that discovery of a ZBG having zinc-binding affinity lower than hydroxamic acid could lead to the identification of isoform-selective HDAC inhibitors, we chose thiol as ZBG for further explorative study on isoform-selective HDAC inhibitors.…”
Section: )mentioning
confidence: 99%